2013
DOI: 10.1080/13623699.2013.813108
|View full text |Cite
|
Sign up to set email alerts
|

Provision of antiretroviral care to displaced populations in humanitarian settings: a systematic review

Abstract: Providing antiretroviral treatment (ART) in humanitarian settings is challenging. Reports suggest that ART provision is feasible, but the evidence base is scarce. We systematically searched three databases for studies reporting ART outcomes among displaced populations in settings of conflict, natural disasters or political instability, and estimated overall mortality using random effects models. Fourteen studies were identified, six in conflict areas, five in areas of post-election violence and three in natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Few studies, however, have sought to rigorously compare HIV treatment outcomes between refugee and host national groups. Previous work has shown high levels of adherence to ART, increases in CD4 counts, and increases in survival among confict-affected populations [4, 5]. In a study comparing urban refugees situated in Kuala Lumpur with Malaysian host nationals, we found comparable levels of viral suppression [6].…”
Section: Introductionsupporting
confidence: 54%
“…Few studies, however, have sought to rigorously compare HIV treatment outcomes between refugee and host national groups. Previous work has shown high levels of adherence to ART, increases in CD4 counts, and increases in survival among confict-affected populations [4, 5]. In a study comparing urban refugees situated in Kuala Lumpur with Malaysian host nationals, we found comparable levels of viral suppression [6].…”
Section: Introductionsupporting
confidence: 54%
“…The medical organisation Médecins Sans Frontières (MSF) reported results from 22 ART programs in conflict or postconflict settings in sub-Saharan Africa, finding that patient outcomes were comparable to those in stable resource-limited settings [3]. These findings were also shown in a systematic review and meta-analysis that found mortality and loss to follow-up (LTFU) of patients on ART in conflict settings after twelve months was 9.0% and 8.1% respectively, which are within the range of mortality and LTFU estimates from stable settings [4].…”
Section: Introductionmentioning
confidence: 57%
“…Since then, it has been established that mass rapes and survival transaction sex affecting IDP and refugee women in recent conflicts [ 21 , 40 – 42 ] may impact HIV prevalence in these vulnerable populations but also affect national HIV prevalence and incidence [ 43 ]. However, because a systematic review of interventions that target antiretroviral care for HIV in displaced populations has documented adequate adherence in IDPs, while also profiling the need for multistakeholder engagement and preparedness, it is clear that HIV test-and-treat interventions with IDPs can be successful, leading to outcomes matching those of stable settings [ 44 ]. Our results show that among the unrepresentative sample of adult IDPs in Northeast Nigeria, HIV prevalence was 1.6% whereas the estimated prevalence of HIV among adults in all 3 states was between 0.4%–1.3% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%